Inflammatory Biomarkers Are Associated With a Decline in Functional Status at Discharge in Children With Acute Respiratory Failure: An Exploratory Analysis - Carlton, Erin F.; Weeks, Heidi M.; Dahmer, Mary K.; Quasney, Michael W.; Sapru, Anil; Curley, Martha A.Q.; Flori, Heidi R. (Critical care explorations, 2021)
Supplemental Digital Content is available in the text. OBJECTIVES: To evaluate the link between early acute respiratory failure and functional morbidity in survivors using the plasma biomarkers interleukin-8, interleukin-1 receptor antagonist, thrombomodulin, and plasminogen activator inhibitor-1. We hypothesized that children with acute respiratory failure with higher levels of inflammation would have worse functional outcomes at discharge, as measured by Pediatric Overall Performance Category. DESIGN: Secondary analysis of the Genetic Variation and Biomarkers in Children with Acute Lung Injury (R01HL095410) study. SETTING: Twenty-two PICUs participating in the multisite clinical trial, Randomized Evaluation of Sedation Titration for Respiratory Failure (U01 HL086622) and the ancillary study (Biomarkers in Children with Acute Lung Injury). SUBJECTS: Children 2 weeks to 17 years requiring invasive mechanical ventilation for acute airways and/or parenchymal lung disease. Patients with an admission Pediatric Overall Performance Category greater than 3 (severe disability, coma, or brain death) were excluded. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Among survivors, 387 patients had no worsening of Pediatric Overall Performance Category at discharge while 40 had worsening functional status, defined as any increase in Pediatric Overall Performance Category from baseline. There was no significant relationship between worsening of Pediatric Overall Performance Category and interleukin-8 or plasminogen activator inhibitor-1 on any day. There was no significant relationship between interleukin-1 receptor antagonist, or thrombomodulin, and worsening Pediatric Overall Performance Category on day 1. Plasma interleukin-1 receptor antagonist and thrombomodulin were significantly elevated on days 2 and 3 in those with worse functional status at discharge compared with those without. In multivariable analysis, interleukin-1 receptor antagonist and thrombomodulin were associated with a decline in functional status on days 2 and 3 after adjustment for age and highest oxygenation index. However, after adjusting for age and cardiovascular failure, only day 2 thrombomodulin levels were associated with a worsening in Pediatric Overall Performance Category. CONCLUSIONS: Higher levels of interleukin-1 receptor antagonist or thrombomodulin following intubation were associated with worse Pediatric Overall Performance Category scores at hospital discharge in children who survive acute respiratory failure. These data suggest that persistent inflammation may be related to functional decline.